Epidemiology of suicidal acute poisonings in adolescents registered at the University Clinic of Toxicology, Skopje - Z. Pereska; D. Chaparoska; N. Bekarovski; N. Zumberi; N. Simonovska; A. Babulovska; K. Naumoski; K. Kostadinovski (My University, 2019)
Background: Adolescent suicidal poisoning is a reflection of serious social and medical problems in young people. The purpose of the study is to analyze the epidemiological profile of acute poisoning in adolescents during nine years period. Method: the study was a retrospective cross-sectional covering registered suicidal poisoning in adolescents (15-19 year) at the Clinic of Toxicology. Material: In the period from 2010 to 2018, a total of 1622 acute poisonings were registered in adolescents. Suicidal motivated poisoning s were observed in 756 patients or 46.6% of all poisonings in adolescents and were significantly more prevalent ( Z=-3.580, P<0.001) in female (84.4%) than male (15.6%) adolescents. The most common were drug poisoning (83.6%), but corrosive intoxications were also significantly represented (11%). The most commonly used medications were benzodiazepines (50,6%). Fewer poisonings with ethyl alcohol (1.9%), chemicals (1.15), pesticides (1.5%), cosmetics (0.8%) and psychoactive substances (0.3%) were reported. The trend of suicidal poisoning in adolescents maintained stable (y=-3.93x+8005,7, R2=0.298, F(1,7)=2.978, P=0.128) as well as the trend of total number of poisonings in this population group (y=-5.433x+11122.95, R2=0.168, F(1,7)=1.411,P=0.274). The average length of hospitalization was 20,6 ±14,9 days. No deaths were reported as a result of poisoning in this population group. Conclusion: The trend of registered poisonings in adolescents has not gone up over the last 9 years with increased susceptibility to females. Measures to reduce suicide attempts in adolescents should be implemented such as improved psychiatric control, prescribing a smaller quantity of medications and reduced availability of corrosives, especially in adolescent at-risk groups.
Keywords: adolescents; suicide; poisoning; self-harm